El nuevo enfoque de la fiscalización ambiental y los riesgos ambientales en las transacciones de M&A - Huertas del Pino Cavero, Luis Felipe (Pontificia Universidad Católica del Perú, 2023)
In this paper the author seeks to provide detailed information on the basis of the new approach to environmental auditing carried out by the Organismo de Evaluación y Fiscalización Ambiental. This audit concerns all those targets that require or have a specific environmental certification. When these companies are part of M&A transactions, buyers or interested parties must carry out the due diligence with special attention to the compliance regarding environmental regulations, since it is currently an aspect of high regulation and potential fines with high amounts. The author emphasizes that if the buyer does not wish to be affected in the future, he should corroborate the cross- cutting information provided by the Administrative Law with the appropriate specialists and tools.

En el presente trabajo, el autor busca brindar información detallada sobre las bases del nuevo enfoque de la fiscalización ambiental realizada por el Organismo de Evaluación y Fiscalización Ambiental. Esta fiscalización atañe a todas aquellas targets que requieren o cuentan con una certificación ambiental específica. Cuando estas empresas son parte de transacciones de M&A, los compradores o interesados deben realizar el due diligence con especial atención a los cumplimientos de regulación ambiental dado que en la actualidad es un aspecto de alta regulación y de potenciales multas con elevadas cuantías. El autor resalta que si el comprador no desea verse afectado en lo posterior, debe corroborar información transversal planteada por el Derecho Administrativo con especialistas y herramientas adecuados.
The new approach to environmental auditing and environmental risks in M&A transactions
Keywords: M&A; Environmental regulation; Target; Due diligence; Auditing; Fusiones y adquisiciones; Regulación ambiental; Target; Due diligence; Fiscalización; https://purl.org/pe-repo/ocde/ford#5.05.01